Knockdown of circ_0025908 inhibits proliferation, migration, invasion, and inflammation while stimulates apoptosis in fibroblast-like synoviocytes by regulating miR-650-dependent SCUBE2 - Ronghua Wang; Hongbo Li; Yunning Han; Lei Li (Taylor & Francis Group, 2022)
Background Circular RNAs (circRNAs) are demonstrated to play vital roles in human diseases, including rheumatoid arthritis (RA). Therefore, this research aimed to explore the effects of hsa_circRNA_0025908 (circ_0025908) on RA. Methods RNA expression of circ_0025908, microRNA-650 (miR-650), and Signal peptide-CUBepidermal growth factor-like containing protein 2 (SCUBE2) were assessed by real-time quantitative polymerase chain reaction; protein expression of SCUBE2, apoptosis- and invasion-related proteins was evaluated by western blot assay. Functional assays were performed using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazol-3-ium bromide, 5-ethynyl-2'-deoxyuridine, transwell, flow cytometry, and enzyme linked immunosorbent assay assays. Dual-luciferase reporter, RNA immunoprecipitation, and RNA pull-down assays confirmed the interaction relationship among circ_0025908, miR-650, and SCUBE2. Results Circ_0025908 was overexpressed in synovial tissues and fibroblast-like synoviocytes (FLS) from RA patients. Inhibition of circ_0025908 repressed proliferation, migration, invasion, inflammation, and cell cycle progression, while induced apoptosis in the FLS isolated from RA patients (FLS-RA), accompanied with increased Bax, cleaved caspase-3 and E-cadherin, but declined Bcl-2, N-cadherin and Vimentin. MiR-650 was a target of circ_0025908, and SCUBE2 was a target for miR-650. Silencing of miR-650 could overturned above effects of circ_0025908 knockdown in FLS-RA, whereas its overexpression could mimic those effects by downregulating SCUBE2. Additionally, SCUBE2 expression could be positively regulated by circ_0025908 and inversely regulated by miR-650. Notably, Pearson's correlation analysis confirmed the linear correlation among circ_0025908, miR-650 and SCUBE2 in these RA tissues. Conclusion Circ_0025908 inhibition can suppress FLS-RA dysfunctions through targeting miR-650/SCUBE2 axis, suggesting a new potential therapeutic clue for RA patients.